Detecting social emotions with a NAO robot - Rincon, J. A. (2016)
This article aims to give an approach of a dynamic and emotional propagation, which allows to calculate the propagation of the emotion of a group of humans and/or intelligent entities. The dynamic model is based on the Newton laws in order to calculate the emotional attraction among them. To obtain the emotions we use a NAO robot as a tool to move around of a real environment for interacting with the humans. The robot obtains the emotions through image processing. Moreover, the robot can start a dialogue game with humans in order to estimate the personality of a new individual.